Analisis Smart School Manajemen Layanan Ujian Akhir Semester Pada Aplikasi Qualitiva menggunakan Framework ITIL Versi 3 di SMA - Yunita Permata Sari; Marutha Berlianti Akbar; Tata Sutabri (Bulletin of Information Technology (BIT), 2023)
Smartschool is a school concept that uses information and communication technology (ICT) to support the learning and assessment process in the classroom. As is the case at SMA Negeri 22 which already uses information technology in the form of online-based exam applications, one of which uses Qualitiva for the end-of-semester exam process. The research was conducted with the aim of improving the quality of service in the Qualitiva online-based exam application. The method used in this research is descriptive qualitative with data collection techniques through interviews and observation. The research results show that the implementation of the ITIL 3 framework in the qualitative online exam application can provide improved service management at SMA Negeri 22 Palembang by using the ITIL 3 Service Management Lifecycle which includes service strategy, service design, service transition, service operations, and service monitoring. Thus, based on the results of the smart school analysis, final semester exam service management in the Qualitiva application using the ITIL version 3 framework at SMA Negeri 22 Palembang can ensure that the services provided meet user needs and can be run effectively and efficiently. Qualitiva is provided by the SMA Negeri School. 22 Palembang based on IT can meet user needs and can be run effectively and efficiently in order to improve school management services at SMA Negeri 22 Palembang.